Geranylgeranoic acid and the MAOB–CYP3A4 axis: a metabolic shift underlying age-related liver cancer risk - Tabata, Yuki (Frontiers in Aging, 2025)
Geranylgeranoic acid (GGA) is a naturally occurring acyclic isoprenoid with chemopreventive effects against hepatocellular carcinoma. In mammals, GGA is endogenously synthesized via the oxidative metabolism of geranylgeraniol by monoamine oxidase B (MAOB). However, MAOB activity decreases with age, leading to reduced hepatic GGA levels. Emerging evidence suggests that cytochrome P450 3A4 (CYP3A4) may compensate for this decline, providing an alternative oxidative pathway in MAOB–deficient conditions. This mini-review summarizes the current findings on GGA biosynthesis and metabolism in the aging liver, focusing on the MAOB–CYP3A4 axis, in which MAOB serves as the primary enzyme for endogenous GGA synthesis and CYP3A4 provides a compensatory pathway under MAOB–deficient conditions, and its relevance to age-related hepatic dysfunction. By discussing recent evidence on enzymatic compensation and age-dependent metabolic changes, this review highlights how the CYP3A4–GGA pathway may help unravel the complexity of hepatic aging. These findings may provide a mechanistic basis for developing preventive strategies targeting age-related hepatocarcinogenesis, particularly in older individuals with reduced MAOB–GGA activity.